2007
DOI: 10.1088/0953-8984/20/03/035219
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of BaPbO3and Ba2PbO4

Abstract: The electronic structure of BaPbO3 and Ba2PbO4 was investigated using photoemission, x-ray diffraction (XRD) and tight binding linear muffin tin orbital (TB-LMTO) band structure techniques. BaPbO3 is a base material for all Pb based superconductors. Rietveld analysis of the XRD data suggested that BaPbO3 is an orthorhombically distorted perovskite with Imma space group and Ba2PbO4 possesses tetragonal structure with I4/mmm space group. LMTO calculations indicated an insulating ground state for Ba2PbO4 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…It is worthwhile to note that the Ba−Pb−O system has many possible stable compounds, including Ba 2 PbO 4 and Ba 2 PbO 6 , and Pb ions may also have a stable valence state of 2+. 48,49 It has been reported that the oxygen vacancies can enable the partial reduction of Pb 4+ to Pb 2+ and the change in the Pb−O bonding angle, which is responsible for the semiconducting behavior of BaPbO 3 . 50,51 In one possible theoretical scenario, Pb 2+ enters the A site, which leads to a situation similar to what is observed with Sr: a small decrease in the lattice constant (<1%) and disordered reduction of octahedral sizes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthwhile to note that the Ba−Pb−O system has many possible stable compounds, including Ba 2 PbO 4 and Ba 2 PbO 6 , and Pb ions may also have a stable valence state of 2+. 48,49 It has been reported that the oxygen vacancies can enable the partial reduction of Pb 4+ to Pb 2+ and the change in the Pb−O bonding angle, which is responsible for the semiconducting behavior of BaPbO 3 . 50,51 In one possible theoretical scenario, Pb 2+ enters the A site, which leads to a situation similar to what is observed with Sr: a small decrease in the lattice constant (<1%) and disordered reduction of octahedral sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical calculations of the energetics for A-site or B-site occupancy provide very similar results and do not discriminate between the two cases. It is worthwhile to note that the Ba–Pb–O system has many possible stable compounds, including Ba 2 PbO 4 and Ba 2 PbO 6 , and Pb ions may also have a stable valence state of 2+. , It has been reported that the oxygen vacancies can enable the partial reduction of Pb 4+ to Pb 2+ and the change in the Pb–O bonding angle, which is responsible for the semiconducting behavior of BaPbO 3 . , …”
Section: Results and Discussionmentioning
confidence: 99%
“…The peak deconvolution of Ti 2p spectra was carried out using the Asymmetric Gassian Lorentzian sum function [10] defined as,…”
Section: Resultsmentioning
confidence: 99%
“…Weakly correlated oxide perovskites of the form ABO 3 , where A is an alkali or alkaline earth element and B = Sn, Pb, Bi, have shown diverse structural polymorphs and electronic properties, including metal-insulator transition, superconductivity, and nontrivial topological phases [1][2][3][4][5][6][7][8] . Among these, the emerging superconducting properties, similar to that exhibited by cuprates, have been investigated extensively in their pristine form or with substitution at A and/or B sites [9][10][11] . BaPb 1−x B x O 3 is one such member in this family which exhibits Drude kind of metallic behaviour in its pristine form (x=0) and superconducting phase upon Bi (0<x≤0.3) substitution at T c = 13 K [12][13][14][15][16][17] .…”
mentioning
confidence: 99%